Predictors of 10-year mortality in a population of community-dwelling Brazilian elderly: the Bambuí cohort study of aging Determinantes da mortalidade em 10 anos de idosos Brasileiros residentes na comunidade: estudo de coorte de idosos de Bambuí - Maria Fernanda Lima-Costa; Sergio Viana Peixoto; Divane L. Matos; Josélia O. A. Firmo; Elizabeth Uchôa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
We used data on 1,399 participants aged 60 and over from the Bambuí Cohort Study of Aging to examine predictors of mortality in a socioeconomically disadvantaged population. From 1997 to 2007, 599 participants died and 6.2% were lost to follow-up, leading to 12,415 person-years (pyrs) of observation. The death rate was 48.3 per 1,000 pyrs. Age (adjusted hazard ratio [HR] = 1.40), male gender (HR = 1.80), never married (HR = 1.78) or a widow (HR = 1.26), poor self-rated health (HR = 1.31), inability to perform four or more activities of daily living (HR = 3.29), number of cardiovascular risk factors (HR = 1.51 for two and HR = 1.91 for three or more), Trypanosoma cruzi infection (HR = 1.27), and number of medications (HR = 1.06) were each significantly (p < 0.05) and independently associated with mortality. The Mini-Mental State Examination score showed a protective effect (HR = 0.96). Except T. cruzi infection, other predictors of mortality were highly consistent with those found in more affluent elderly populations. Foram utilizadas informações de 1.399 participantes (> 60 anos) do Estudo de Coorte de Idosos de Bambuí, para examinar os determinantes da mortalidade em uma população com nível socioeconômico baixo. Entre 1997 e 2007, 599 participantes faleceram e 6,2% foram perdidos para acompanhamento, resultando em 12.415 pessoas-ano de observação. A taxa de mortalidade foi de 48,3 por mil pessoas-ano. Idade (hazard ratio ajustada [HR] = 1,40), sexo masculino (HR = 1,80), ser solteiro (HR = 1,78) ou viúvo (HR = 1,26), pior autoavaliação da saúde (HR = 1,31), incapacidade para realizar quatro ou mais atividades da vida diária (HR = 3,29), número de fatores de risco cardiovascular (HR = 1,51 para dois e HR = 1,91 para três ou mais), infecção pelo Trypanosoma cruzi (HR = 1,27) e número de medicamentos (HR = 1,06) apresentaram associações significantes (p < 0,05) e independentes com o evento. O escore do Mini-Exame do Estado Mental mostrou efeito protetor (HR = 0,96). Exceto a infecção pelo T. cruzi, os outros preditores da mortalidade foram consistentes com o observado em populações idosas com melhor situação socioeconômica.